Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 28456 by mondodotto@gmail.com last updated on 26/Jan/18

Commented by Tinkutara last updated on 26/Jan/18

5

Answered by Rasheed.Sindhi last updated on 26/Jan/18

f(2)=5,f(3)=4,g(2)=5,g(3)=2,g(4)=1  .−.−.−.−.  f( g(3) )=f(2)    ∵ g(3)=2                  =5          ∵ f(2)=5

f(2)=5,f(3)=4,g(2)=5,g(3)=2,g(4)=1.....f(g(3))=f(2)g(3)=2=5f(2)=5

Terms of Service

Privacy Policy

Contact: info@tinkutara.com